2015
DOI: 10.1002/pd.4569
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal examination of the area and morphology of the atrioventricular valves using four-dimensional ultrasound in normal and abnormal hearts

Abstract: Prenatal examination of the morphology and area of the AV valves using four-dimensional ultrasound is feasible. A rectangular valve opening is normal, which was visualized in about one third of the normal fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Systematic analysis of the areas and morphologic characteristics of the semilunar valves using 4D sonography with STIC is feasible in normal fetal hearts and fetal hearts with congenital heart disease. Comparable to our earlier study of the atrioventricular valves, 9 the valve opening and valve shape could be visualized in almost every STIC volume with good quality (96.1% in normal hearts and 97.4% in abnormal hearts). Although visualization of the valve leaflets is feasible, the success rates were lower than expected.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Systematic analysis of the areas and morphologic characteristics of the semilunar valves using 4D sonography with STIC is feasible in normal fetal hearts and fetal hearts with congenital heart disease. Comparable to our earlier study of the atrioventricular valves, 9 the valve opening and valve shape could be visualized in almost every STIC volume with good quality (96.1% in normal hearts and 97.4% in abnormal hearts). Although visualization of the valve leaflets is feasible, the success rates were lower than expected.…”
Section: Discussionsupporting
confidence: 58%
“…The project was designed to examine the morphologic characteristics of the fetal heart using 4D sonography. We described the morphologic characteristics and areas of the atrioventricular valves and the differential insertion of the atrioventricular valves earlier 9 , 10 . This study focused on the morphologic characteristics and areas of the semilunar valves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is abundant literature detailing quantitative and qualitative assessments of many aspects of the fetal heart . Late‐gestation fetal cardiac assessment has also been described by some, and this study adds to the existing literature by quantifying atrial and atrioventricular valve disproportions and their associations with other findings, including aneurysms of the septum primum, tricuspid valve insufficiency, and mild flow aberrations in the ductal and aortic arches in late gestation.…”
Section: Discussionmentioning
confidence: 93%
“…From the STIC acquisition, three‐dimensional voxels were created that had an X, Y, and Z component, resulting in three simultaneously displayed images referred to as the A, B, and C planes (Figure ). Following the first publication describing the STIC technique, numerous studies have been reported describing the use of this technique for evaluation of fetal cardiovascular structures and function …”
Section: Introductionmentioning
confidence: 99%